2018
DOI: 10.4108/eai.13-7-2018.163574
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Mining and Analysis of Specific Groups (Political and Regional) by using API

Abstract: People have informal conversations on social media sites (Twitter, Facebook, etc) that shed light on the current issues around the world-opinions, and concerns about the learning process. Data from such environments can provide valuable information to predict the future to make effective decision making, however, the usage of such data is challenging. The complexity of such data from social media content requires the use of human understanding as well as social network analysis to make predictions. We focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Hence performance has the potential to ensure satisfactory results and actions to be achieved (44) and thus to identify its position in terms of a strong and weak point through the evaluation of a proven MME performance. In addition, the purpose of the evaluation of SME performance is to improve the range of opportunities (45) , whether internal or external, to achieve the overall potential best and to achieve desirable development over time (45) . The research model shown below in the Figure 1 has one exogenous variable that is entrepreneurial marketing strategies with four dimensions; proactive orientations, innovativeness, focus on customer and value creation.…”
Section: Entrepreneurial Marketing Strategies and Smes Performancementioning
confidence: 99%
“…Hence performance has the potential to ensure satisfactory results and actions to be achieved (44) and thus to identify its position in terms of a strong and weak point through the evaluation of a proven MME performance. In addition, the purpose of the evaluation of SME performance is to improve the range of opportunities (45) , whether internal or external, to achieve the overall potential best and to achieve desirable development over time (45) . The research model shown below in the Figure 1 has one exogenous variable that is entrepreneurial marketing strategies with four dimensions; proactive orientations, innovativeness, focus on customer and value creation.…”
Section: Entrepreneurial Marketing Strategies and Smes Performancementioning
confidence: 99%